W. E. B. du Bois: Toward Agnosticism, 1868-1934 - Johnson, Brian L. (Rowman & Littlefield Publishers, 2008)
Brian L. Johnson's remarkable biography of W.E.B. Du Bois describes the evolution of religious views from Du Bois's birth until his resignation as editor of Crisis magazine in 1934. W.E.B. Du Bois: Toward Agnosticism, 1868-1934 traces Du Bois's mounting skepticism through his earliest church experiences to his sociological training in Berlin culminating with his writings in Crisis magazine. Johnson argues that despite Du Bois's frequent use of Protestant religious rhetoric, the mature Du Bois was a critic of African American religious organizations and their leaders, and a scientifically oriented agnostic who did not adhere to any religious orthodoxy.